PROMOTIONAL MEDIA DESIGN FOR SARASWATI IV KINDERGARTEN DENPASAR TO INCREASE BRAND AWARENESS - I Gusti Ngurah Agung Dewantara; I Ketut Sutarwiyasa; I Wayan Adi Putra Yasa (Journal of Aesthetics, Design, and Art Management, 2025)
Purpose: Saraswati IV Kindergarten, Denpasar, as an early childhood education institution, has faced a decline in student enrollment in recent years due to limited promotional media. This study aims to design a profile video for Saraswati IV Kindergarten, Denpasar, as a promotional medium capable of conveying institutional information in an informative, persuasive, and engaging manner to parents of prospective students. Research methods: The method used in this research is qualitative, with data collection techniques including observation, interviews, documentation, and literature review. The video profile design process involved pre-production, production, and post-production, applying visual communication design principles and cinematography techniques appropriate to the characteristics of early childhood education. Findings: The research results show that the designed profile video comprehensively and communicatively represents the identity, advantages, facilities, and learning methods of Saraswati IV Kindergarten, Denpasar. Furthermore, supporting media such as brochures, billboards, hats, and carousel content also strengthen the integrated promotional strategy. Implications: It is hoped that the design of this profile video will increase the visibility of the institution and become an effective promotional tool in attracting the interest of parents of prospective students.